Development of microcomputer-assisted instructional aid in library and information science a case study - Tasanaporn Gadavanij (Institute of Library Science, University of the Philippines Diliman, 1983)
An attempt was made to develop a computer-assisted instruction (CAI) aid in library and information science. Specifically, it includes a report on the background, approaches to and methods of designing and developing a CAI package for COMPAIS version II-A, release no. 1 as well as prepare a software package and related documentation for a CAI module implemented on a TRS-80 Model II for the "Online Operations" submodule of COMPAIS version II-A, release no. 1.